A detail simulation of reactivity controlled compression ignition combustion strategy in a heavy-duty diesel engine run on natural gas/diesel fuel. (September 2018) - Ebrahimi, Mojtaba; Najafi, Mohammad; Jazayeri, Seyed Ali; Mohammadzadeh, Ali Reza
The aim of this study is to investigate in details the effects of a number of combustion parameters to optimize the reactivity controlled compression ignition operation running on natural gas and diesel fuel. In the present work, a single-cylinder heavy-duty diesel engine with a specially modified bathtub piston bowl profile for reactivity controlled compression ignition operation is studied and simulated through commercial software. A broad load range from 5.6 to 13.5 bar indicated mean effective pressure at a constant engine speed of 1300 r/min, fixed amount of diesel fuel mass, and with no exhaust gas recirculation is considered. The results from the developed model confirm that the model can accurately simulate the reactivity controlled compression ignition combustion. Also, by focusing on the time of formation of certain important radicals in combustion, the start of combustion and the time of natural gas dissociation are accurately predicted. Furthermore, the influence of some parameters such as different diesel fuel injection strategies, intake temperature, and intake pressure on the reactivity controlled compression ignition combustion is evaluated and the limitation of the engine operation at low temperature combustion is investigated.